Presentación. Populismo: miradas críticas desde AméricaLatina sobre el legado teórico de Ernesto Laclau - Nazareno, Marcelo; Magrini, Ana Lucía; Reynares, Juan Manuel (Studia Politicae, 2024)
No posee